2020
DOI: 10.1155/2020/2861978
|View full text |Cite
|
Sign up to set email alerts
|

Luteolin Protects Pheochromocytoma (PC‐12) Cells against Aβ25-35‐Induced Cell Apoptosis through the ER/ERK/MAPK Signalling Pathway

Abstract: The regulatory effect of luteolin on the progression of Alzheimer’s disease (AD) remains unclear from the perspective of apoptosis. The present study aimed to investigate the protective effects of luteolin against Aβ25-35-induced cell apoptosis in pheochromocytoma (PC-12) cells. Aβ25-35 was used to induce an in vitro model of AD. Estradiol was used as a positive control. The PC-12 cells were incubated with luteolin alone or in combination with fulvestrant or U0126. The results showed that luteolin treatment si… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 33 publications
0
10
0
Order By: Relevance
“…A high amount of LUT may have potential toxicity, inhibiting Aβ25-35 and inducing cell apoptosis. It also activates the ER/ERK/MAPK signaling pathway to protect Bcl2 cells against Aβ25-35 and induce apoptosis via specifically acting on ERβ [93]. Luteolin may decrease brain insulin resistance.…”
Section: Protection Against Alzheimer's Diseasementioning
confidence: 99%
“…A high amount of LUT may have potential toxicity, inhibiting Aβ25-35 and inducing cell apoptosis. It also activates the ER/ERK/MAPK signaling pathway to protect Bcl2 cells against Aβ25-35 and induce apoptosis via specifically acting on ERβ [93]. Luteolin may decrease brain insulin resistance.…”
Section: Protection Against Alzheimer's Diseasementioning
confidence: 99%
“…However, MAPK signaling pathway disorder is one of pathways that cause oxidative damage ( Yao et al, 2019 ). Previous studies reported that Lut upregulated the expression of p-ERK1/2 and MAPK, suggesting Lut alleviate oxidative stress by activating the MAPK signaling pathway ( Wu et al, 2015 ; Wang et al, 2020 ). In this study, Lut treatment increased the developmental competence of PA and IVF embryos.…”
Section: Discussionmentioning
confidence: 94%
“…Accordingly, luteolin exhibited great activities in improving CNS disorders and cognitive impairments induced by diabetes or chronic cerebral hypoperfusion. , In AD, luteolin was found to improve the memory and learning impairments in both Aβ- and STZ-induced models. As an example, Yu et al reported that luteolin (50–200 mg/kg) suppressed the oxidative stress and improved the cholinergic system of Aβ 1–40 -injected rats as evidenced by the increased ChAT activity and inhibited AChE activity in luteolin-treated group . Besides, an in vitro study indicated that luteolin reduced Aβ 25–35 -induced mitochondrial apoptosis in PC12 cells by activation of an estrogen receptor (ERβ) and extracellular signal-regulated kinase 1/2 (ERK1/2) . Moreover, it was found that luteolin improved fibrillary Aβ 1–40 (fAβ)-induced neuroinflammatory effects and BBB dysfunction .…”
Section: Neuroprotective Flavonoids In Mung Beanmentioning
confidence: 95%
“…(ERβ) and extracellular signal-regulated kinase 1/2 (ERK1/ 2). 56 Moreover, it was found that luteolin improved fibrillary Aβ 1−40 (fAβ)-induced neuroinflammatory effects and BBB dysfunction. 57 Furthermore, neuroprotective activity of luteolin was also observed in a transgenic Drosophila model.…”
Section: ■ Neuroprotective Flavonoids In Mungmentioning
confidence: 99%